Vibrational spectroscopic characterization of the magnesium borate-phosphate mineral lüneburgite. Issue 9 (20th October 2016) - Korybska-Sadło, Iwona; Sitarz, Maciej; Król, Magdalena; Gunia, Piotr
ABSTRACT: Lüneburgite, a rare magnesium borate-phosphate mineral from Mejillones, Chile, has been characterized using Raman and mid-infrared spectroscopy methods. Boron tetrahedra are characterized by sharp Raman band at 877 cm −1, attributed to the ν1 [BO4 ] 5− symmetric stretching mode. The phosphate anion is associated with a distinct band at 1032 cm −1, attributed to the ν3 [PO4 ] 3− antisymmetric stretching mode. The most intensive Raman band at 734 cm −1 is ascribed to stretching vibrations of bridging oxygen atoms in boron–oxygen–phosphor bridges. Bonds associated with water bending mode and stretching vibration are observed at 1661 cm −1 (infrared) and in the 3000–3500 cm −1 region (Raman and infrared spectrum).